Effects of Nuclear Polyhedrosis Virus (NPV) on The Death of Spodoptera litura Larvae (Lepidoptera: Noctuidae) and its Comparison with Chemical Pesticide - Agung Sih Kurnianto; Ana Miftahul Janah; Nur Laila Magvira; Ankardiansyah Pandu Pradana (Techno: Jurnal Penelitian, 2022)
Spodoptera litura larvae are polyphagous insects and have caused a lot of damage to various commodities. The application of Nuclear Polyhedrosis Virus (NPV) can be used as an alternative to control, other than by using chemical pesticides. This research was conducted to compare the mortality of S. litura with NPV treatment and compare them with chemical pesticides. NPV treatment with a concentration of 0.3% is used to soak the leaves to be used as larvae feed, as well as chemical pesticides the active ingredient Lambda-cyhalothrin (with a concentration of 0.05%). Observations were made at 2, 24, 48, and 76 hours after application. The parameters observed from the treatment included the percentage of mortality and morphological changes of larvae. Observation of the morphological changes of larvae was carried out by the parameters of slowing motion, discoloration, decaying, and severe shrinkage. Based on the results of the comparison, the percentage of mortality in the treatment of chemical pesticides is higher than the NPV. Death of 100% in Lambda-Cyhalothrin treatment was recorded in the first 2 (two) hours, while for NPV treatment is as much as 80%. The larvae with NPV treatment undergo a process of color change and the decomposition process is faster than the treatment of Lambda-cyhalothrin.